Respuesta :
Given the equation:
[tex]f(x)=6x^{2}+12x-7[/tex]
The question is: What are the zeros of this quadratic function? this happens when f(x) = 0, so:
[tex]f(x)=6x^{2}+12x-7=0[/tex]
a = 6
b = 12
c = -7
Then the zeros are given through equation:
[tex]x_{12}= \frac{-b\pm \sqrt{b^{2}-4ac}}{2a}= \frac{-12\pm \sqrt{12^{2}-4(6)(-7)}}{2(6)}[/tex]
∴ [tex]x_{1}=0.47[/tex]
[tex]x_{2}=-2.47[/tex]
[tex]f(x)=6x^{2}+12x-7[/tex]
The question is: What are the zeros of this quadratic function? this happens when f(x) = 0, so:
[tex]f(x)=6x^{2}+12x-7=0[/tex]
a = 6
b = 12
c = -7
Then the zeros are given through equation:
[tex]x_{12}= \frac{-b\pm \sqrt{b^{2}-4ac}}{2a}= \frac{-12\pm \sqrt{12^{2}-4(6)(-7)}}{2(6)}[/tex]
∴ [tex]x_{1}=0.47[/tex]
[tex]x_{2}=-2.47[/tex]
Solution:
Thus, the zeros are x=0.47,-2.47
Explanation:
We have been given the function
[tex]f(x)=6x^2+12x-7[/tex]
In order to find the zeros of this function, we will solve the quadratic equation [tex]f(x)=6x^2+12x-7=0[/tex]
We'll solve this by quadratic formula which is given by
[tex]x_{1,\:2}=\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]
We have
[tex]a=6,\:b=12,\:c=-7:[/tex]
On substituting these values, we get
[tex]x_{1,\:2}=\frac{-12\pm \sqrt{12^2-4\cdot \:6\left(-7\right)}}{2\cdot \:6}\\\\x_{1,\:2}=\frac{-12\pm \sqrt{312}}{2\cdot \:6}\\x_{1,\:2}=\frac{-12\pm 2\sqrt{78}}{12}\\\\\mathrm{The\:final\:solutions\:to\:the\:quadratic\:equation\:are:}\\\\x=\frac{\sqrt{78}-6}{6},\:x=-\frac{6+\sqrt{78}}{6}\\\text{In decimal, we have}\\x=0.47,-2.47[/tex]
Thus, the zeros are x=0.47,-2.47